Partition Property of Domain Decomposition Without Ellipticity (Journal of Computational Mathematics, 2001)
Partition property plays a central role in domain decomposition methods. Existing theory essentially assumes certain ellipticity. We prove the partition property for problems without ellipticity which are of practical importance. Example applications include implicit schemes applied to degenerate parabolic partial differential equations arising from superconductors, superfluids and liquid crystals. With this partition property, Schwarz algorithms can be applied to general non-elliptic problems with an $h$-independent optimal convergence rate. Application to the time-dependent Ginzburg-Landau model of superconductivity is illustrated and numerical results are presented.
Keywords: Partition property; Domain decomposition; Non-ellipticity; Degenerate parabolic problems; Time-dependent Ginzburg-Landau model; Superconductivity; Preconditioning; Schwarz algorithms.